Development of a bacterial bioassay for atrazine and cyanuric acid detection - Hua, Anna; Gueuné, Hervé; Cregut, Mickaël; Thouand, Gérald; Durand, Marie-José (Frontiers in Microbiology, 2015)
The s-triazine herbicides are compounds which can disseminate into soils and water. Due to their toxic effects on living organisms, their concentrations in drinking water are legislated by WHO recommendations. Here we have developed for the first time, to the best of our knowledge, an alternative method for physicochemical quantification using two bioluminescent bacterial biosensors: E. coli SM003 for cyanuric acid detection and E. coli SM004 for both atrazine and cyanuric acid detection. The concentration of cyanuric acid detection for E. coli SM003 ranges from 7.83 µM to 2.89 mM, and for E. coli SM004 ranges from 0.22 µM to 15 µM. Moreover, atrazine detection by E. coli SM004 ranges from 1.08 µM to 15 µM. According to WHO recommendations, the cyanuric acid detection range is sensitive enough to discriminate between polluted and drinking water. Nevertheless, the detection of atrazine by E. coli SM004 is only applicable for high concentrations of contaminants.